2021
DOI: 10.20916/1812-3228-2021-4-55-66
|View full text |Cite
|
Sign up to set email alerts
|

Interdiscourse Switching in Drama Text. Gaze Patterns and Comprehension Check Results

Abstract: The study explores the cognitive process of interdiscourse switching which occurs in reading drama plays with the author’s discourse fragments incorporated (Areas of Interest). The oculographic experiment reveals the gaze patterns and the discourse interpretation patterns, more and less typical of the process. The experiment is preceded by the parametric and annotation analysis of interdiscourse switching construal. Interestingly, there exist several construal parameter groups contingent with eye movement load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The proposed Event-modelling Framework is grounded in cognitive linguistics construal theories [22,32] which have been implemented in experimental studies [7,19], although the construal operations are scarcely if ever observed on a systemic basis. For instance, EMF was tested in eye tracking research in [10] where it allowed to determine the effects of space construal and agentivity in textual descriptions presented together with the images.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed Event-modelling Framework is grounded in cognitive linguistics construal theories [22,32] which have been implemented in experimental studies [7,19], although the construal operations are scarcely if ever observed on a systemic basis. For instance, EMF was tested in eye tracking research in [10] where it allowed to determine the effects of space construal and agentivity in textual descriptions presented together with the images.…”
Section: Related Workmentioning
confidence: 99%